2016
DOI: 10.1002/nau.23151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pelvic floor muscle activity during running in continent and incontinent women: An exploratory study

Abstract: Running appears to trigger pre-activation before and reflex-activation after heel-strike and should therefore not only be regarded with caution due to its SUI related effects. Running training stimuli may serve as a beneficial complement to a PFM training rationale, leading to reflex activity of the pelvic floor muscles, when used in sense of power training methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
58
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 39 publications
4
58
0
5
Order By: Relevance
“…Physical activity and coughing are known to manifest SUI 41,42 and it was shown that maximal EMG activity of the PFM is reached at about 120 ms after the impact of coughing 43 or running. 28 Taking into account that the FVC in the present study demonstrated the peak activity after about 500 ms, it has to be questioned, whether the strategy/training of FVC can at all contribute to continence. Although the time to peak activity during FVC seems long, it still may contribute to the preparation of the quicker reflexive responses.…”
Section: Discussionmentioning
confidence: 67%
“…Physical activity and coughing are known to manifest SUI 41,42 and it was shown that maximal EMG activity of the PFM is reached at about 120 ms after the impact of coughing 43 or running. 28 Taking into account that the FVC in the present study demonstrated the peak activity after about 500 ms, it has to be questioned, whether the strategy/training of FVC can at all contribute to continence. Although the time to peak activity during FVC seems long, it still may contribute to the preparation of the quicker reflexive responses.…”
Section: Discussionmentioning
confidence: 67%
“…14 The mean EMG pre-activity and reflex activity increased with speed. Of note, EMG values during running in women with stress urinary incontinence exceeded 100% of activity during maximum voluntary contraction at the highest speed of 15 km/hour.…”
Section: Literature Updatementioning
confidence: 95%
“…19,20 Concurrent EMG recordings of the same sample that were published previously did not confirm a relaxation before T0. 21 On the contrary, high EMG values were shown in the 30 ms time interval before heelstrike, which is also the time interval where both feet are off the ground.…”
Section: Discussionmentioning
confidence: 94%
“…For the activity 30 ms after heel-strike high EMG values have been demonstrated, 21 which allows assumption of a concentric muscle action. Heel-strike seems to be a "turningpoint" which terminates the caudal displacement and initiates a quick concentric action.…”
Section: Discussionmentioning
confidence: 99%